Updates to the RIFM Criteria Document for fragrance ingredient evaluation - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2-propanol, 1,1′,1′,1'-(1,2-ethanediyldinitrilo)tetrakis-, CAS Registry Number 102-60-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, octyl crotonate, CAS Registry Number 22874-79-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, propenylguaethol, CAS Registry Number 94-86-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, ethyl 3-hydroxybutyrate, CAS Registry Number 5405-41-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3-(p-tert-butylphenyl)-2-methylpropanol, CAS Registry Number 56107-04-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, ethyl 3-hydroxyhexanoate, CAS Registry Number 2305-25-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, linoleic acid, CAS Registry Number 60-33-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, β-naphthyl isobutyl ether, CAS Registry Number 2173-57-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 1,5-dimethylhexyl acetate, CAS Registry Number 67952-57-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3-(4-methyl-3-pentenyl)-3-cyclohexene-1-carbonitrile, CAS Registry Number 68084-04-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, cyclohexaneethyl acetate, CAS Registry Number 21722-83-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 3,5,5-trimethylcyclohexanol, CAS Registry Number 116-02-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 5-methyl-2-phenyl-2-hexenal, CAS Registry Number 21834-92-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 4-heptanol, 2,6-dimethyl-,acetate, CAS Registry Number 10250-45-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, phenylacetaldehyde glyceryl acetal, CAS Registry Number 29895-73-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, cyclohexanemethanol, 2,4-dimethyl-, CAS Registry Number 68480-15-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2,2,6-trimethylcyclohexanone, CAS Registry Number 2408-37-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, cis-4-(isopropyl)cyclohexanemethanol, CAS registry number 13828-37-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, cyclohexanone, 2-ethyl-4,4-dimethyl-, CAS registry number 55739-89-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, squalene, CAS Registry Number 111-02-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, β-guaiene, CAS Registry Number 88-84-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 3-hexene, 1,1′,''-[ethylidynestris(oxy)]tris-, (3Z, 3′Z,3"Z)-, CAS registry number 215305-10-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl 3-hydroxyhexanoate, CAS Registry Number 21188-58-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 4-methyl-2-phenyl-2-pentenal, CAS Registry Number 26643-91-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 2-phenyl-2-butenal, CAS Registry Number 4411-89-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, dodecyldimethylamine oxide, CAS Registry Number 1643-20-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, tricosane, CAS Registry Number 638-67-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl 2-nonenoate, CAS registry number 111-79-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 4-(isopropyl)-β-methylcyclohexanethanol, CAS Registry Number 67634-03-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Delivery of liothyronine by microneedle patch for the treatment of hypothyroidism - Yasmine Gomaa; Tasnuba Hasin; Martin N. Griffin; Thy C. Nguyen; Richard K. Noel; Laura O’Farrell; Elizabeth A. McAninch; Ann Marie Kaiser; Levi B. Wood; Mark R. Prausnitz (Drug Delivery and Translational Research, 2026)

RIFM fragrance ingredient safety assessment, undecanol, CAS Registry Number 30207-98-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl cis-5-octenoate, CAS Registry Number 41654-15-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl 3-nonenoate, CAS Registry Number 13481-87-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 4-methyl-3-penten-2-one, CAS Registry Number 141-79-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl 3-hexenoate, CAS Registry Number 2396-78-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Identifying a new candidate space crop: the alpine strawberry Fragaria vesca - K. Nakashima; C. Farrell; J. Calabria; A. H. Millar; G. Massa; M. Watt (Life Sciences in Space Research, 2026)

RIFM fragrance ingredient safety assessment, 1-(1,2,3,4,5,6,7,8-octahydro-2,3,8,8-tetramethyl-2-naphthalenyl)ethanone, CAS Registry Number 54464-57-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, docosane, CAS Registry Number 629-97-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl jasmonate, CAS Registry Number 1211-29-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2-isobutyl-4-methyltetrahydro-2H-pyran-4-ol, CAS Registry Number 63500-71-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, dimyrcene, CAS Registry Number 532-87-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, methyl myristate, CAS Registry Number 124-10-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, cyclohexane, 1-ethenyl-1-methyl-2,4-bis(1-methylethenyl)-, (1R,2R,4S)-rel-, CAS Registry Number 33880-83-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl myristate, CAS Registry Number 124-06-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2-methylpentyl 2-methylvalerate, CAS Registry Number 90397-38-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, pyrazine, methyl (methylthio)-, CAS Registry Number 67952-65-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 2-propenoic acid, 2-[1-(3,3-dimethylcyclohexyl)ethoxy]-2-methylpropyl ester, CAS Registry Number 820975-49-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, hexadecyl palmitate, CAS Registry Number 540-10-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, cyclohexane, 1-ethenyl-1-methyl-2-(1-methylethenyl)-4-(1-methylethyl)-, didehydro derivative, CAS Registry Number 68845-33-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, acetyl cedrene, CAS Registry Number 32388-55-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, butyl sulfide, CAS Registry Number 544-40-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, heneicosane, CAS Registry Number 629-94-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl palmitate, CAS Registry Number 628-97-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, sclareol, CAS registry number 515-03-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl octadecanoate, CAS Registry Number 111-61-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, cyclohexyl methyl pentanone, CAS Registry Number 4927-39-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, heptadecane, CAS Registry Number 629-78-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, hexadecane, CAS Registry Number 544-76-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, oleic acid, CAS Registry Number 112-80-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, pentadecane, CAS Registry Number 629-62-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, tetradecane, CAS Registry Number 629-59-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, nonadecane, CAS Registry Number 629-92-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, octadecane, CAS Registry Number 593-45-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, eicosane, CAS Registry Number 112-95-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessments, ethyl ricinoleate, CAS Registry Number 55066-53-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 4-methyl-8-methylenetricyclo[3.3.1.(3,7)]decan-2-yl acetate, CAS Registry Number 122760-85-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

From kelp forests to turf reefs: Patterns, drivers, and impacts to functional diversity - Shane P. Farrell; Dara S. Yiu; Stuart K. Ryan; Rene D. Francolini; Courtney E. Stuart; Jonathan S. Lefcheck; Yasmina M. Shah Esmaeili; Douglas B. Rasher (Ecology, 2026)
Kelp forests are declining in many regions due to ocean warming, predator loss, and other anthropogenic stressors. In areas of rapid ocean warming, including the southern Gulf of Maine, these ecosystems have transitioned to a novel state dominated by low‐lying mats of turf algae. However, the pace, drivers, and ecological consequences of this transition remain unclear. Here, we used field surveys from 32 sites over 5 years (2018–2023) to reveal a continuation of kelp forest collapse and northward expansion of turf algae across Maine's coast. Next, we united data on benthic cover with key environmental variables in a structural equation model to show that turf algae were directly enhanced by higher ocean temperatures and decreased wave disturbance and indirectly enhanced by a warming‐induced loss of kelp cover. Lastly, we revealed the shift from kelp to turf yielded a seaweed assemblage dominated by traits associated with rapid growth, high surface area‐to‐volume ratios, and markedly reduced canopy height, indicating declines in habitat provisioning and carbon storage with kelp forest loss. Our findings highlight the accelerating impacts of climate change on temperate reef ecosystems and the vital services they provide. Further, we provide insights into a new state shift that is now occurring globally and underscore the need for urgent actions to mitigate further loss of foundational kelp forests.

RIFM fragrance ingredient safety assessment, phytyl acetate, CAS Registry Number 10236-16-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, [2,2-bis[(3,7-dimethyl-2,6-octadienyl)oxy]ethyl]benzene, CAS Registry Number 67634-02-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 2,3,5,6-tetramethylpyrazine, CAS Registry Number 1124-11-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, cedryl methyl ether, CAS Registry Number 67874-81-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, methyl 2-(formylamino)benzoate, CAS Registry Number 41270-80-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, naphtho[2,1-b]furan, dodecahydro-3a,6,6,9a-tetramethyl-, (3aR,5aS,9aS,9bR)-, CAS Registry Number 6790-58-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, laurel leaf oil, CAS Registry Number 8007-48-5, RIFM ID 476-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, (Z)-2-penten-1-ol, CAS Registry Number 1576-95-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 6-methyl-3,5-heptadien-2-one, CAS Registry Number 1604-28-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isopropylphenylbutanal, CAS Registry Number 125109-85-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, methyl cinnamate, CAS Registry Number 103-26-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, lovage leaf oil, CAS Registry Number 8016-31-7, RIFM ID 813-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, β,β,3-trimethyl benzenepropanol, CAS Registry Number 103694-68-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, dihydro-β-ionone, CAS registry number 17283-81-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3-hexanone, CAS Registry Number 589-38-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl methylphenylglycidate, CAS Registry Number 77-83-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, dihydro-α-ionone, CAS Registry Number 31499-72-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, hinoki root oil, CAS Registry Number 91745-97-0, RIFM ID 5487-A2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isobornyl methyl ether, CAS Registry Number 5331-32-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl safranate, CAS registry number 35044-57-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, Bucchu oil, betulina, CAS Registry Number 68650-46-4, RIFM ID 73-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, ethyl pyruvate, CAS registry number 617-35-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, thyme oil, red, CAS Registry Number 8007-46-3, RIFM ID 471.E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 2-methyl-3-tolylpropionaldehyde, CAS Registry Number 41496-43-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, dihydrocarvyl acetate, CAS Registry Number 20777-49-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3,7-dimethyl-2,6-nonadien-1-al, CAS Registry Number 41448-29-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isopulegyl acetate, CAS Registry number 57576-09-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, anisyl alcohol, CAS Registry Number 105-13-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, bicyclo[3.1.0]hexan-3-one, 4-methyl-1-(1-methylethyl)-, CAS Registry Number 1125-12-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 6-isopropyl-2(1H)-octahydronaphthalenone, CAS Registry Number 34131-98-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl 3-phenylglycidate, CAS Registry Number 121-39-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, citral, CAS Registry Number 5392-40-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 1,6-octadien-3-ol, 3,7-dimethyl-, acid-isomerized, CAS Registry Number 73018-51-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 1,1-dimethoxycyclododecane, CAS Registry Number 950-33-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2-ethyl-5-methoxybicyclo[2.2.1]heptane, CAS registry number 122795-41-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, styrax absolute, CAS registry Number 8024-01-9, RIFM ID 6877.K2.1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, α,α-dimethyl-p-ethylphenylpropanal, CAS Registry Number 67634-15-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, α-hexylcinnamaldehyde, CAS Registry Number 101-86-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-octalactone, CAS Registry number 104-50-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 4-methoxybenzoic acid, CAS Registry Number 100-09-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3-methyl-2-butenyl acetate, CAS Registry Number 1191-16-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-hexalactone, CAS Registry Number 695-06-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, myristic acid, CAS Registry Number 544-63-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isobutyric acid, CAS Registry Number 79-31-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-decalactone, CAS Registry Number 706-14-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-undecalactone, CAS Registry Number 104-67-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isovaleric acid, CAS Registry Number 503-74-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-nonalactone, CAS Registry Number 104-61-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

2nd update to RIFM fragrance ingredient safety assessment, 3,7-dimethyl-1,6-nonadien-3-ol, CAS Registry Number 10339-55-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

2nd update to RIFM fragrance ingredient safety assessment, linalool, CAS Registry number 78-70-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2H-indeno[4,5b] furan, decahydro-2,2,6,6,7,8,8-heptamethyl, CAS Registry Number 476332-65-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, γ-dodecalactone, CAS Registry Number 2305-05-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, palmitic acid, CAS Registry number 57-10-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2,6,8-trimethylnonan-4-one, CAS Registry Number 123-18-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylbutyric acid, CAS Registry number 116-53-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4,8-dimethyl-4,9-decadienal, CAS Registry number 71077-31-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cedrene, CAS Registry Number 11028-42-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 5-methyl-3-heptanone, CAS Registry Number 541-85-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, iris pallida oil, CAS registry number 8002-73-1, RIFM ID 265.A2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 8H-indeno(4,5-B)furan,2,3,3a,4,5,5a,6,7,8a,9-decahydro-2,6,6,7,8,8-hexamethyl mixture of isomers, CAS Registry Number 338735-71-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-nonanone, CAS Registry Number 821-55-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-undecanone, CAS Registry Number 112-12-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-octanone, CAS registry number 106-68-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-decanone, CAS Registry Number 693-54-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-heptanone, CAS Registry Number 110-43-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, γ-heptalactone, CAS Registry Number CAS # 105-21-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, γ-valerolactone, CAS Registry Number 108-29-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, lauric acid, CAS Registry Number 143-07-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-octanone, CAS Registry Number 111-13-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, benzoin infusion, Sumatra, CAS Registry Number 9000-05-9, RIFM ID 104-K2.31 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4-heptanone, CAS Registry Number 123-19-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-heptanone, CAS Registry Number 106-35-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, myrtenol, CAS Registry Number 515-00-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-phenylpropionic acid, CAS registry number 501-52-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, hexyl phenylacetate, CAS Registry Number 5421-17-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methyl cyclohexadiene (mixture of isomers), CAS Registry Number 30640-46-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, decanoic acid, CAS Registry Number 334-48-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 5-methyl-5-propyl-2-(1-methylbutyl)-1,3-dioxan, CAS Registry Number 80480-24-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, octanoic acid, CAS Registry Number 124-07-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, p-isopropylacetophenone, CAS Registry Number 645-13-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, nonanoic acid, CAS Registry Number 112-05-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4H-4a,9-methanoazuleno[5,6-d]-1,3-dioxole, octahydro-2,2,5,8,8,9a-hexamethyl-, (4aR,5R,7aS,9R)-, CAS Registry Number 211299-54-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, spiro[5.5]undec-8-en-1-one, 2,2,7,9-tetramethyl-, CAS Registry Number 502847-01-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, p-tolyl 3-methylcrotonate, CAS Registry Number 24700-20-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, hexanoic acid, CAS Registry Number 142-62-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-4-phenyl-1,3-dioxolane, CAS Registry Number 33941-99-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-hydroxyacetophenone, CAS Registry Number CAS # 118-93-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4-isopropyl-2-methoxy-1-methylbenzene, CAS Registry Number 6379-73-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 1-ethynylcyclohexyl acetate, CAS Registry Number 5240-32-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4,4a,5,9b-tetrahydroindeno[1,2-d]-1,3-dioxine, CAS Registry Number 18096-62-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-phenyl-1-propanol, CAS Registry Number 122-97-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzaldehyde, CAS Registry Number 100-52-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Recognizing, reinforcing, and strengthening community capacity through researcher–community partnerships: insights from EPA researchers’ engagements with communities in four US waterscapes - Megan Dwyer Baumann; Kathleen C. Williams; Emily Eisenhauer; Desiree Farrell; Jenna M. Hartley; Meghan R. Klasic; A. Marissa Matsler; Candace K. May; Leah M. Sharpe; Abigail Sullivan; Kara Takasaki; Kathleen Torso; et al. (Socio-Ecological Practice Research, 2025)

Applications of vessel positional data in next-generation stock assessments - Chollett; S. O’Farrell; L. Perruso; S.R. Sagarese; C. Liese; K. Dettloff (Fisheries Research, 2025)

RIFM fragrance ingredient safety assessment, benzeneacetonitrile, a-butylidene-, (Z), CAS Registry Number 130786-09-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, geraniol, CAS registry number 106-24-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-phenoxyethanol, CAS Registry number 122-99-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, cinnamyl alcohol, CAS Registry Number 104-54-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzyl alcohol, CAS Registry Number 100-51-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, benzoic acid, 2-[[3-(4-methoxyphenyl)-2-methylpropylidene]amino]-, methyl ester, CAS registry number 111753-62-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

2nd update to RIFM fragrance ingredient safety assessment, 4-carvomenthenol, CAS Registry Number 562-74-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-tert-butylcyclohexyl acetate, CAS registry number 88-41-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-tert-butylcyclohexyl acetate, CAS Registry Number 31846-06-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-tert-butylcyclohexyl acetate, CAS Registry Number 32210-23-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Aboveground succulence in woody plants is related with drought survival in green roof modules and not their degree of anisohydry or water use - Bihan Guo; Stefan K. Arndt; Rebecca E. Miller; Claire Farrell (Plant and Soil, 2025)

What doesn’t kill you makes you stronger: Using plant traits to inform species selection for naturalistic plantings in hotter and drier climates - Lavinia Hsiao-Hsuan Chu; Christopher Szota; Stefan K. Arndt; Claire Farrell (Landscape and Urban Planning, 2025)

RIFM fragrance ingredient safety assessment, phenyl salicylate, CAS Registry Number 118-55-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, fenchone, CAS Registry Number 1195-79-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, phenethyl acetate, CAS registry number 103-45-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, hydroxycitronellal diethyl acetal, CAS Registry Number 7779-94-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, amylcyclohexyl acetate (mixed isomers), CAS Registry Number 67874-72-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, octanal dimethyl acetal, CAS Registry Number 10022-28-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, linalyl hexanoate, CAS Registry Number 7779-23-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylundecanal dimethyl acetal, CAS Registry Number 68141-17-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, hydroxycitronellal dimethyl acetal, CAS Registry number 141-92-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-isobutylquinoline, CAS registry number 93-19-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-methyl quinoline, CAS registry number 91-63-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 1,1-diethoxyisooctane, CAS Registry Number 69178-43-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, nonane, 1,1-diethoxy-, CAS Registry Number 54815-13-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1,1-diethoxy-3,5,5-trimethylhexane, CAS registry number 86198-35-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-(methylpropyl)quinoline, CAS registry number 1333-58-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, decanal dimethyl acetal, CAS Registry Number 7779-41-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-isopropylphenol, CAS Registry Number 99-89-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3-buten-2-one, 4-(2,2,3-trimethyl-6-methylenecyclohexyl)-, CAS registry number 79-68-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, heptanal dimethyl acetal, CAS registry number 10032-05-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 1,1-diethoxyhexane, CAS registry number 3658-93-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-acetyl-5-methylfuran, CAS Registry Number 1193-79-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isophytol, CAS Registry Number 505-32-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-furyl methyl ketone, CAS Registry Number 1192-62-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, savory winter oil, CAS Registry Number 90106-57-3, RIFM ID 1181-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, ho wood oil, CAS Registry Number 8022-91-1, RIFM ID 217-D2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, dimethylcyclohex-3-ene-1-carbaldehyde (isomer unspecified), CAS Registry Number 27939-60-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 6-methyl-2-(4-methyl-3-cyclohexen-1-yl)-5-hepten-2-ol, CAS Registry Number 515-69-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, maltol, CAS registry number 118-71-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3-(5,5,6-trimethylbicyclo[2.2.1]hept-2-yl)cyclohexan-1-ol, CAS registry number 3407-42-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzyl valerate, CAS Registry Number 10361-39-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isocyclocitral, CAS Registry Number 1335-66-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, ho leaf oil, CAS Registry Number 8022-91-1, RIFM ID 217-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, ho bark oil, CAS registry number 8022-91-1, RIFM ID 217-C2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzyl formate, CAS Registry Number 104-57-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 1,1-diethoxyheptane, CAS Registry Number 688-82-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-octanol, CAS registry number 111-87-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4,4a,6,7,8,8a-hexahydro-1,4-methanonaphthalen-5(1H)-one, CAS Registry Number 51519-65-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, amyl hexanoate, CAS registry number 540-07-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, undecanal, CAS Registry Number 112-44-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, N-benzoylanthranilic acid, CAS Registry Number 579-93-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, undecyl alcohol, CAS Registry Number 112-42-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-tridecanol, CAS Registry Number 112-70-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, lauryl alcohol, CAS Registry Number 112-53-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, hexyl alcohol, CAS Registry Number 111-27-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, ethyl maltol, CAS Registry Number 4940-11-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, butyrophenone, CAS Registry Number 495-40-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, p-tolyl phenylacetate, CAS Registry Number 101-94-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methyl decanoate, CAS Registry Number 110-42-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-decanol, CAS registry number 112-30-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, clove bud absolute, CAS Registry Number 8000-34-8, RIFM ID 583-F2.1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, nonyl alcohol, CAS Registry Number 143-08-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methoxy dicyclopentadiene carboxaldehyde, CAS Registry Number 86803-90-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, octahydro-4,7-methano-1H-indenecarbaldehyde, CAS Registry Number 30772-79-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, acetophenone, CAS Registry number 98-86-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, Sage oil, Spanish, CAS Registry Number 8022-56-8, RIFM ID 479-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

2nd Update to RIFM fragrance ingredient safety assessment, α-amylcinnamaldehyde, CAS Registry Number 122-40-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Corrigendum to “RIFM fragrance ingredient safety assessment, vanillin isobutyrate, CAS Registry Number 20665-85-4” [Food Chem. Toxicol. 197 Supplement 1 (2024) 115141 ISSN 0278–6915] - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, heptyl alcohol, CAS registry number 111-70-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-acetoxy-2,5-dimethyl-3(2H)furanone, CAS Registry Number 4166-20-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl propionate, CAS Registry Number 105-68-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isobutyl propionate, CAS Registry Number 540-42-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-(p-methoxyphenyl)-2-butanone, CAS Registry Number 104-20-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cis-6-nonenal, CAS registry number 2277-19-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-phenylbutanal, CAS registry number 16251-77-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Linking functional responses and effects with stoichiometric traits - Eric K. Moody; Katie Anania; Kate S. Boersma; Tyler J. Butts; Jessica R. Corman; Spencer Cruz; W. Reilly Farrell; Kauan N. Fonseca; Amy C. Krist; Erin I. Larson; Alex Lewanski; Christian Liriano; et al. (Ecology, 2025)
Trait‐based approaches to study biodiversity responses to changing environmental conditions have become popular because these approaches provide context to how and why certain taxa shift in abundance within an assemblage. Trait‐based approaches also offer the potential to link shifts in assemblage composition to effects on ecosystem functions like rates of primary production, detrital decomposition, and nutrient uptake. However, focusing on response traits in multidimensional functional diversity studies limits our ability to make these linkages. We developed a multidimensional analytical and visual stoichiometric diversity framework that links organismal responses to and effects on environmental change using stoichiometric traits. We define these traits as the acquisition, assimilation, allocation, and excretion of key chemical elements by members of an assemblage. We discuss the considerations for using stoichiometric traits in a trait‐based framework and apply the framework to case studies of temporal variation in stream benthic invertebrate assemblages and spatial variation in urban woody vegetation assemblages. These examples illustrate the utility of the stoichiometric diversity framework for testing stoichiometric hypotheses and suggest promising linkages between assemblage shifts and shifts in ecosystem function.

Update to RIFM fragrance ingredient safety assessment, cyclohexanepropanol, α-ethyl-2,2,6-trimethyl-, CAS Registry Number 60241-52-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methyl 3,7-dimethyl-6-octenoate, CAS registry number 2270-60-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, (1aα,4α,7aα)-1a,3,3,4,6,6-hexamethyl-1a,2,3,4,5,6,7,7a-octahydronapth[3,3-b]oxirene, CAS Registry Number 94400-98-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cyclododecyl formate, CAS Registry Number 59052-82-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, (Z)-4-dodecenal, CAS registry number 21944-98-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-phenylpropionaldehyde, CAS registry number 93-53-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4,5-dihydro-3(2H)thiophenone, CAS Registry Number 1003-04-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 9-undecenal, CAS Registry Number 143-14-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, β-methyl-benzenepentanal, CAS registry number 55066-49-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, nonanal, CAS registry number 124-19-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, trans-4-decen-1-al, CAS Registry Number 65405-70-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl formate, CAS Registry Number 110-45-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 8-undecenal, CAS registry number 58296-81-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, linalyl isovalerate, CAS Registry Number 1118-27-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, hexanal, CAS Registry Number 66-25-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4,8-dimethyl-7-nonen-2-ol, CAS Registry Number 40596-76-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-ethoxy-4-(methoxymethyl)phenol, CAS Registry Number 5595-79-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, β-caryophyllene alcohol, CAS registry number 472-97-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, acetylcarene, CAS Registry Number 3608-11-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-heptenal, CAS Registry Number 6728-31-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl alcohol, CAS Registry Number 123-51-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-phenoxyethyl isobutyrate, CAS registry number 103-60-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, linalyl isobutyrate, CAS Registry Number 78-35-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-tetradecanol, CAS Registry Number 112-72-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3-hexenoic acid, CAS Registry Number 4219-24-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methyl 2-nonynoate, CAS Registry Number 111-80-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3-(4-methyl-3-cyclohexenyl)butanol, CAS Registry Number 15760-18-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, dihydro-β-ionol, CAS Registry Number 3293-47-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, p-tolylacetaldehyde, CAS Registry Number 104-09-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, β-pinene, CAS Registry Number 127-91-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, geranyl crotonate, CAS Registry Number 56172-46-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-4(2,2,3-trimethyl-3-cyclopentenyl)butanol, CAS Registry Number 72089-08-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-methylbutyl valerate, CAS Registry Number 2050-09-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, octanal, CAS Registry Number 124-13-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, tricyclo[3.3.1.1.(3.7)]decan-2-ol, 4-methyl-8-methylene-, CAS Registry Number 122760-84-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, heptanal, CAS registry number 111-71-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylbutyl butyrate, CAS Registry Number 51115-64-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, amyl alcohol, CAS Registry Number 71-41-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, pentanoic acid, 2-methylbutyl ester, CAS Registry Number 55590-83-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3,4-xylenol, CAS Registry Number 95-65-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylbutyl acetate, CAS Registry Number 624-41-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isobutyl butyrate, CAS Registry Number 539-90-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, decanal, CAS registry number 112-31-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cedryl formate, CAS Registry Number 39900-38-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-(4-methoxyphenyl)-3-methylbutan-2-one, CAS Registry Number 67828-19-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-(p-methoxyphenyl)-2-propanone, CAS Registry Number 122-84-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, trans-2-hexenyl acetate, CAS Registry Number 2497-18-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, isolongifolene oxide, CAS Registry Number 26619-69-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, p-menth-8-en-2-one, CAS Registry Number 7764-50-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, l-menthyl (R,S)-3-hydroxybutyrate, CAS Registry Number 108766-16-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, butyl alcohol, CAS registry number 71-36-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, tridecanal, CAS registry number 10486-19-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cedr-8-ene epoxide, CAS Registry Number 13567-39-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, geranyl tiglate, CAS Registry Number 7785-33-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4′-tert-butyl-2′,6′-dimethylacetophenone, CAS Registry Number 2040-10-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, ethyl trans-2,cis-4-decadienoate, CAS registry number 3025-30-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl acetate, CAS Registry Number 123-92-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-hexadecanol, CAS Registry Number 36653-82-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isobutyl acetate, CAS Registry Number 110-19-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cis-3-hexenyl salicylate, CAS Registry Number 65405-77-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-2-hepten-6-ol, CAS registry number 1569-60-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, nopyl acetate, CAS registry number 128-51-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl butyrate, CAS Registry Number 106-27-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, piperonal, CAS Registry Number 120-57-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzothiazole, CAS Registry Number 95-16-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-cyclopropylmethyl-4-methoxybenzene, CAS registry number 16510-27-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3,7-dimethyl-2-methylenocta-6-enal, CAS registry number 22418-66-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isobutyl alcohol, CAS Registry Number 78-83-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylpropyl pentanoate, CAS Registry Number 10588-10-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-(3-heptyl)-1,3-dioxolane, CAS Registry Number 4359-47-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, ethyl 2-methyl-3-pentenoate, CAS Registry Number 1617-23-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, vanillin isobutyrate, CAS Registry Number 20665-85-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-methylbutanal diethyl acetal, CAS Registry Number 3842-03-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Review of APSIM's soil nitrogen modelling capability for agricultural systems analyses - Kirsten Verburg; Heather R. Pasley; Jody S. Biggs; Iris Vogeler; Enli Wang; Henrike Mielenz; Val O. Snow; Chris J. Smith; Chiara Pasut; Andrea D. Basche; Di He; Sotirios V. Archontoulis; et al. (Agricultural Systems, 2025)

Microbial communities in biosolids-amended soils: A critical review of high-throughput sequencing approaches - Cameron J. Reid; Mark Farrell; Jason K. Kirby (Journal of Environmental Management, 2025)

RIFM fragrance ingredient safety assessment, (4-methylphenoxy)acetaldehyde, CAS Registry Number 67845-46-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, propyl alcohol, CAS Registry Number 71-23-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, dibenzyl ether, CAS Registry number 103-50-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, β-ionyl acetate, CAS Registry Number 22030-19-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cinnamyl cinnamate, CAS Registry Number 122-69-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2,6-xylenol, CAS Registry Number 576-26-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isobutyl formate, CAS registry number 542-55-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl 2-octynoate, CAS Registry Number 111-12-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexanone 1,3-butylene glycol ketal, CAS Registry Number 6413-26-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, zingerone, CAS Registry Number 122-48-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-ethoxy-4-[(1-methylethoxy)methyl] phenol, CAS Registry number 96840-56-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, diethyl malonate, CAS registry number 105-53-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-(4,8-dimethylnona-3,7-dienyl)pyridine, CAS Registry Number 38462-23-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,3-propanediol, 2,2-dimethyl-, 1,3-diacetate, CAS registry number 13431-57-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3-(cis-3-hexenyloxy)propanenitrile, CAS Registry Number 142653-61-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isobutyl benzoate, CAS registry number 120-50-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-(4-methyl-3-penten-1-yl)-2(5H)-furanone, CAS Registry number 61315-75-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-butyl-4,4,6-trimethyl-1,3-dioxane, CAS registry number 54546-26-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-(2-tert-butyl cyclohexyloxy)-2-butanol, CAS Registry Number 139504-68-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl 2-methylbutyrate, CAS Registry Number 7452-79-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, benzyl salicylate, CAS registry number 118-58-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl benzoate, CAS registry number 6789-88-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl isovalerate, CAS Registry Number 556-24-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, cyclohexanecarboxylic acid, CAS Registry Number 98-89-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl isobutyrate, CAS registry number 97-62-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 6,8-dimethylnonan-2-ol, CAS registry number 70214-77-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isoamyl benzoate, CAS registry number 94-46-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl isobutyrate, CAS registry number 547-63-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 10-undecenoic acid, heptyl ester, CAS registry number 68141-27-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3-(4-methylcyclohex-3-enyl)-3-butenyl acetate, CAS registry number 6819-19-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, p-methyl-α-amyl cinnamic aldehyde, CAS Registry Number 84697-09-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, methyl salicylate, CAS registry number 119-36-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl 2-methylbutyrate, CAS Registry Number 868-57-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, amyl salicylate, CAS Registry Number 2050-08-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-methyl-2-(1-methylpropyl)cyclohexyl acetate, CAS Registry number 72183-75-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cis-3-hexenyl benzoate, CAS Registry Number 25152-85-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isoamyl salicylate, CAS Registry Number 87-20-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-oxaspiro[4.5]decan-2-one, 8-(1-methylethyl)-, trans-, CAS Registry Number 4625-90-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-methyl-2-pentanol, CAS registry number 108-11-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2,6-dimethyl-4-heptanol, CAS registry number 108-82-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, heptyl acetate, CAS registry number 112-06-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

A genome assembly and transcriptome atlas of the inbred Babraham pig to illuminate porcine immunogenetic variation - John C. Schwartz; Colin P. Farrell; Graham Freimanis; Andrew K. Sewell; John D. Phillips; John A. Hammond (Immunogenetics, 2024)
The inbred Babraham pig serves as a valuable biomedical model for research due to its high level of homozygosity, including in the major histocompatibility complex (MHC) loci and likely other important immune-related gene complexes, which are generally highly diverse in outbred populations. As the ability to control for this diversity using inbred organisms is of great utility, we sought to improve this resource by generating a long-read whole genome assembly and transcriptome atlas of a Babraham pig. The genome was de novo assembled using PacBio long reads and error-corrected using Illumina short reads. Assembled contigs were then mapped to the porcine reference assembly, Sscrofa11.1, to generate chromosome-level scaffolds. The resulting TPI_Babraham_pig_v1 assembly is nearly as contiguous as Sscrofa11.1 with a contig N50 of 34.95 Mb and contig L50 of 23. The remaining sequence gaps are generally the result of poor assembly across large and highly repetitive regions such as the centromeres and tandemly duplicated gene families, including immune-related gene complexes, that often vary in gene content between haplotypes. We also further confirm homozygosity across the Babraham MHC and characterize the allele content and tissue expression of several other immune-related gene complexes, including the antibody and T cell receptor loci, the natural killer complex, and the leukocyte receptor complex. The Babraham pig genome assembly provides an alternate highly contiguous porcine genome assembly as a resource for the livestock genomics community. The assembly will also aid biomedical and veterinary research that utilizes this animal model such as when controlling for genetic variation is critical.

Sprouting Readers© -- Nurturing Potential, Empowering Lives - C. Farrell; J. Wilson; J. Mao; E. Li; K. Li (Journal of the Academy of Nutrition and Dietetics, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-5-phenylpentanol, CAS Registry Number 25634-93-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl formate, CAS registry number 629-33-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl butyrate, CAS Registry Number 2639-63-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, furfural, CAS Registry Number 98-01-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, octyl acetate, CAS Registry Number 112-14-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, octyl formate, CAS registry number 112-32-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-oxaspiro[4.5]decan-2-one, 8-ethyl-, trans-, CAS Registry Number 91069-40-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, p-mentha-1,8-dien-7-ol, CAS Registry Number 536-59-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 7-isopropyl-1,4-dimethylazulene, CAS registry number 489-84-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-isopropyl-1-methylcyclohexene, CAS registry number 29350-67-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl α-ionone, CAS Registry Number 79-78-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, lauryl acetate, CAS Registry Number 112-66-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-oxaspiro[4.5]decan-2-one, 8-methyl-, CAS Registry number 94201-19-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-methyl-5-phenylpentanol, CAS Registry Number 55066-48-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, nonyl acetate, CAS registry number 143-13-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, octyl butyrate, CAS Registry Number 110-39-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-(methylthio)hexyl acetate, CAS registry number 51755-85-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2,2-dimethyl-3-phenylpropanol, CAS registry number 13351-61-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-(cis-3-hexenyl)dihydro-5-methyl-2(3H)furanone, CAS Registry Number 70851-61-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, o-phenyl anisole, CAS registry number 86-26-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, geranyl acetate, CAS registry number 105-87-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, geranyl linalool, CAS registry number 1113-21-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ionone (mixed isomers), CAS registry number 8013-90-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl salicylate, CAS Registry Number 118-61-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-phenyl-3-buten-2-ol, CAS registry number 17488-65-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isopropyl acetate, CAS registry number 108-21-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl propionate, CAS Registry Number 2445-76-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, α-butylcinnamaldehyde, CAS registry number 7492-44-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, decyl acetate, CAS Registry Number 112-17-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, musk ketone, CAS registry number 81-14-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, veratraldehyde, CAS Registry Number 120-14-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isopropyl butyrate, CAS Registry Number 638-11-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-hydroxybenzoic acid, CAS Registry Number 69-72-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-methylfurfural, CAS registry number 620-02-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl acetate, CAS registry number 142-92-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-4-phenylpentanol, CAS registry number 92585-24-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-4-phenylbutyraldehyde, CAS Registry Number 40654-82-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cis-3-hexenal, CAS Registry Number 6789-80-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, pinus nigra oil, CAS Registry Number 8000-26-8, RIFM ID 1068-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexyl phenylacetate, CAS Registry Number 42288-75-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3,4,5,6,6-pentamethylheptan-2-ol, CAS registry number 87118-95-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,3-cyclohexadiene-1-carboxylic acid, 4,6,6-trimethyl-, ethyl ester, CAS Registry Number 100520-15-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2(4H)-benzofuranone, 5,6-dihydro-3,6-dimethyl-, CAS Registry Number 80417-97-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, β-methylphenethyl alcohol, CAS Registry Number 1123-85-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, N-ethyl-N-(3-methylphenyl)propionamide, CAS Registry Number 179911-08-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl cinnamate, CAS Registry number 1866-31-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-hexene, 1-[(2-methyl-2-propenyl)oxy]- (3Z)-, CAS Registry Number 292605-05-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, lavandin abrialis, CAS registry number 8022-15-9, RIFM ID 1048554 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, rotundone, CAS Registry Number 18374-76-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methylheptenol, CAS Registry Number 1335-09-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,4-bis(ethoxymethyl)cyclohexane, CAS Registry Number 54889-63-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, bicyclo[2.2.1]heptan-2-ol, 1,3,3-trimethyl-, benzoate, CAS Registry Number 55066-54-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methylbutyl hexanoate, CAS registry Number 2601-13-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, propanoic acid, 2-methyl-, cyclohexyl ester, CAS Registry Number 1129-47-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3,7-dimethyl-1,6-nonadien-3-yl acetate, CAS Registry Number 61931-80-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-heptanol, 3,6-dimethyl-, CAS registry number 1247790-47-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl cyclohexanecarboxylate, CAS Registry Number 3289-28-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, linalyl butyrate, CAS Registry Number 78-36-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 6-butyl-2,4-dimethyldihydropyrane, CAS Registry Number 24237-00-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3,7-dimethyl-7-methoxyoctan-2-ol, CAS registry number 41890-92-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-isopropyl-N,2,3-trimethylbutyramide, CAS registry number 51115-67-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, piperonyl acetate, CAS registry number 326-61-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, α-propylphenethyl alcohol, CAS registry number 705-73-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl heptanoate, CAS registry number 142-19-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-(4-methylphenoxy)ethanol, CAS Registry Number 15149-10-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, nonanoyl 4-hydroxy-3-methoxybenzylamide, CAS Registry Number 2444-46-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl hexanoate, CAS Registry Number 123-68-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, phenethyl alcohol, CAS Registry Number 60-12-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, benzenepropanol, a,ß-dimethyl-, CAS Registry Number 56836-93-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-(2-oxopropyl)-2-pentylcyclopentanone, CAS Registry Number 40942-73-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1,3,3-trimethyl-2-norbornanyl acetate, CAS registry number 13851-11-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, tetrahydrogeranial, CAS Registry Number 5988-91-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, isobornyl acetate, CAS Registry Number 125-12-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, nerolidyl acetate (isomer unspecified), CAS registry number 2306-78-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, oxacyclohexadecane-2,13-dione, CAS registry number 38223-29-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, (Z)-octadec-9-enol, CAS registry number 143-28-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, linalyl acetate, CAS registry number 115-95-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-naphthalenol, 1,2,3,4,4a,5,8,8a-octahydro-2,2,6,8-tetramethyl-, CAS Registry Number 103614-86-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3a,4,5,6,7,7a-hexahydro-4,7-methano-1H-inden-5-yl pivalate, CAS Registry Number 68039-45-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3a,4,5,6,7,7a-hexahydro-4,7-methano-1H-inden-5-yl isobutyrate, CAS Registry Number 67634-20-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, tricyclodecanyl acetate, CAS registry number 64001-15-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isobornyl propionate, CAS Registry Number 2756-56-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl octanoate, CAS Registry Number 4230-97-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, linalyl formate, CAS registry number 115-99-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, nerol oxide, CAS Registry Number 1786-08-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, l-menthyl D-lactate, CAS registry number 59259-38-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, linalyl propionate, CAS registry number 144-39-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, trichloromethyl phenyl carbinyl acetate, CAS Registry number 90-17-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-hexen-1-ol, 5-methyl-2-(1-methylethenyl)-, CAS registry number 58461-27-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, dihydro-α-terpineol, CAS Registry Number 498-81-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-hexylcyclopentanone, CAS registry number 13074-65-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-4-phenyl-2-butyl isobutyrate, CAS registry number 10031-71-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, d,l-menthone 1,2-glycerol ketal, CAS Registry Number 63187-91-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-cyclohexyl-2-methyl-2-butanol, CAS registry number 83926-73-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4′-hydroxy-3′-methoxyacetophenone, CAS Registry Number 498-02-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2,2,4-trimethyl-4-phenyl-butane-nitrile, CAS Registry Number 75490-39-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, thymol, CAS Registry Number 89-83-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl cinnamate, CAS Registry Number 103-36-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-methyl-2-butenyl benzoate, CAS Registry Number 5205-11-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methylcyclooctyl carbonate, CAS Registry Number 61699-38-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-p-tolylethanol, CAS registry number 699-02-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3,7-dimethyl-1,3,6-octatriene, CAS Registry Number 13877-91-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,1-dimethyl-2-phenylethyl isobutyrate, CAS Registry Number 59354-71-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, amyl cinnamate, CAS Registry Number 3487-99-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-4-phenyl-2-butanol, CAS Registry Number 103-05-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, benzenepropanenitrile, 4-ethyl-α,α.-dimethyl-, CAS Registry Number 134123-93-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, methyl 2,4-dihydroxy-m-toluate, CAS Registry Number 33662-58-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2H-1,5-benzodioxepin-3(4H)-one, 7-(1-methylethyl)-, CAS Registry Number 950919-28-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl 2-ethylhexanoate, CAS Registry Number 2983-37-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexyl salicylate, CAS registry number 25485-88-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment,α-methylbenzyl alcohol, CAS registry number 98-85-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-isopropylcyclohexanol, CAS Registry Number 4621-04-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, acetaldehyde, diphenethyl acetal, CAS Registry Number 122-71-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, α,α-dimethylphenethyl alcohol, CAS Registry Number 100-86-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, citronellyl ethyl oxalate, CAS Registry Number 60788-25-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl 2-tert-butylcyclohexyl carbonate, CAS Registry Number 67801-64-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl 2,3,6-trimethylcyclohexyl carbonate, CAS Registry Number 93981-50-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3-octyl acetate, CAS registry number 4864-61-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, exo-2-[(1,7,7-trimethylbicyclo[2.2.1]hept-2-yl)oxy]ethanol, CAS Registry Number 7070-15-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-propanol, reaction products with boron trifluoride and 5-ethylidenebicyclo[2.2.1]hept-2-ene, CAS registry number 90530-04-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1-propanol, 2-methyl-3-[(1,7,7-trimethylbicyclo-[2.2.1]hept-2-yl)oxy]-, CAS Registry Number 128119-70-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,3-nonanediol acetate (mixed esters), CAS Registry Number 1322-17-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3,12-tridecadienenitrile, CAS Registry Number 134769-33-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexanoic acid, 4-methyl-, CAS registry number 1561-11-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-ethyloctanoic acid, CAS registry number 16493-80-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methylhexanoic acid, CAS registry number 4536-23-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methylheptanoic acid, CAS registry number 1188-02-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, butyl 2-methylvalerate, CAS Registry Number 6297-41-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, N,N-diethyloctamide, CAS registry number 996-97-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, phenethyl salicylate, CAS Registry Number 87-22-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, benzonitrile, 3,4-dimethyl-, CAS Registry Number 22884-95-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-allyl-2-methoxyphenyl benzyl ether, CAS Registry Number 57371-42-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3,6-nonadien-1-ol, CAS Registry Number 76649-25-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl 2-methylpentanoate, CAS Registry Number 39255-32-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, linalyl cinnamate, CAS registry number 78-37-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl 3,5,5-trimethylhexanoate, CAS Registry Number 67707-75-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-methyloctanoic acid, CAS Registry Number 54947-74-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, butyl 10-undecenoate, CAS Registry Number 109-42-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methylvaleric acid, CAS Registry Number 97-61-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3-methylpentanoic acid, CAS registry number 105-43-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-methylnonanoic acid, CAS Registry Number 45019-28-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-ethylbutyric acid, CAS Registry Number 88-09-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cis- and trans-p-1(7),8-menthadien-2-yl acetate, CAS registry number 71660-03-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, diethyldimethylcyclohex-2-en-1-one, CAS Registry Number 68845-36-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-phenyl-3-buten-1-yl acetate, CAS Registry Number 7306-12-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, spiro[1,3-dioxolane-2,8′(5′H)-[2H-2,4a]methanonaphthalene],hexahydro-1′,1′,5′,5′-tetramethyl-, [2′S-(2′α,4′aα,8′aα)]-, CAS Registry Number 154171-77-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, p-tolyl alcohol, CAS Registry Number 589-18-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-methylpentanoic acid, CAS Registry Number 646-07-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-ethyl-2,3,4,5-tetramethylcyclohexen-1-one, CAS Registry Number 17369-60-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexanol, 2-methoxy-4-propyl-, CAS Registry Number 23950-98-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl 10-undecenoate, CAS Registry Number 692-86-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, p-tert-butyldihydrocinnamaldehyde, CAS Registry Number 18127-01-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, isoeugenyl phenylacetate, CAS registry number 120-24-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-(p-isopropylphenyl)propionaldehyde, CAS registry number 7775-00-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3,3,5-trimethylcyclohexyl ethyl ether, CAS Registry Number 67583-77-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, triethyltrimethyl-2-cyclohexen-1-one, CAS Registry Number 68845-35-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, germacrene D, CAS Registry Number 23986-74-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-methyl-2-thiophenecarboxaldehyde, CAS registry number 13679-70-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, isoeugenyl benzyl ether, CAS Registry Number 120-11-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, pentyl benzoate, CAS Registry Number 2049-96-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl vanillin isobutyrate, CAS Registry Number 188417-26-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, l-carvone, CAS Registry Number 6485-40-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, butyl benzoate, CAS Registry Number 136-60-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, p-isopropyl phenylacetaldehyde, CAS Registry Number 4395-92-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl benzoate, CAS Registry Number 93-58-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexane, 1-(1,1-dimethylpropyl)-4-ethoxy-, cis-, CAS Registry Number 181258-87-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-methyl-3-decen-5-ol, CAS Registry Number 81782-77-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isoeugenol, CAS registry number 97-54-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 10-undecen-1-yl acetate, CAS Registry Number 112-19-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-2-pentenoic acid, CAS Registry Number 16957-70-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 6,10-dodecadienal, 3,7,11-trimethyl-, (3S,6E)-, CAS registry number 194934-66-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, cuminyl nitrile, CAS registry number 13816-33-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, (Z,Z)-1,1'-[ethylidenebis(oxy)]di(hex-3-ene), CAS Registry number 63449-64-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl benzoate, CAS Registry Number 93-89-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-methyl-5-phenyl-3-hexanone, CAS Registry Number 4927-36-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, (E)-1-(1-methoxypropoxy)hex-3-ene, CAS Registry Number 97358-54-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl undec-10-enoate, CAS registry number 111-81-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, acetaldehyde ethyl cis-3-hexenyl acetal, CAS Registry Number 28069-74-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, α-amylcinnamaldehyde, CAS Registry Number 122-40-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 9-decenyl acetate, CAS Registry Number 50816-18-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, phenol, 4-(3,6-dihydro-4-methyl-2H-pyran-2-yl)-2-methoxy-, CAS Registry Number 128489-02-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, eucalyptol, CAS Registry Number 470-82-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, pyridine, 5-hexyl-2-methyl-, CAS Registry Number 710-40-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, dodecahydro-3,8,8,11a-tetramethyl-5H-3,5a-epoxynaphth[2,1-c]oxepin, CAS Registry Number 57345-19-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-3-buten-2-ol, CAS Registry Number 115-18-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, o-toluenethiol, CAS Registry Number 137-06-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, benzoic acid, 2-hydroxy-5-methyl-, methyl ester, CAS Registry Number 22717-57-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, linalool oxide, CAS Registry Number 1365-19-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Stable carbon and nitrogen isotopes explain methylmercury concentrations in stream food webs of Lake George, New York (USA) - M. W. Swinton; P. K. Myer; M. F. Schaller; E. A. Pettitt; J. L. Farrell; S. A. Nierzwicki-Bauer (Ecotoxicology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Assessing the risk of human‐to‐wildlife pathogen transmission for conservation and public health - Anna C. Fagre; Lily E. Cohen; Evan A. Eskew; Max Farrell; Emma Glennon; Maxwell B. Joseph; Hannah K. Frank; Sadie J. Ryan; Colin J Carlson; Gregory F. Albery (Ecology Letters, 2022)
The SARS‐CoV‐2 pandemic has led to increased concern over transmission of pathogens from humans to animals, and its potential to threaten conservation and public health. To assess this threat, we reviewed published evidence of human‐to‐wildlife transmission events, with a focus on how such events could threaten animal and human health. We identified 97 verified examples, involving a wide range of pathogens; however, reported hosts were mostly non‐human primates or large, long‐lived captive animals. Relatively few documented examples resulted in morbidity and mortality, and very few led to maintenance of a human pathogen in a new reservoir or subsequent “secondary spillover” back into humans. We discuss limitations in the literature surrounding these phenomena, including strong evidence of sampling bias towards non‐human primates and human‐proximate mammals and the possibility of systematic bias against reporting human parasites in wildlife, both of which limit our ability to assess the risk of human‐to‐wildlife pathogen transmission. We outline how researchers can collect experimental and observational evidence that will expand our capacity for risk assessment for human‐to‐wildlife pathogen transmission.

Year-round acoustic monitoring of Antarctic blue and fin whales in relation to environmental conditions off the west coast of South Africa - Ishmail S. Letsheleha; Fannie W. Shabangu; Dara Farrell; Rex K. Andrew; Philip L. la Grange; Ken P. Findlay (Marine Biology, 2022)

Host‐pathogen‐environment interactions predict survival outcomes of adult sockeye salmon ( Oncorhynchus nerka ) released from fisheries - Amy K. Teffer; Scott G. Hinch; Kristina M. Miller; David. A. Patterson; Arthur L. Bass; Steven J. Cooke; Anthony P. Farrell; Terry D. Beacham; Jacqueline M. Chapman; Francis Juanes (Molecular Ecology, 2022)
Incorporating host‐pathogen(s)‐environment axes into management and conservation planning is critical to preserving species in a warming climate. However, the role pathogens play in host stress resilience remains largely unexplored in wild animal populations. We experimentally characterized how independent and cumulative stressors (fisheries handling, high water temperature) and natural infections affected the health and longevity of released wild adult sockeye salmon ( Oncorhynchus nerka ) in British Columbia, Canada. Returning adults were collected before and after entering the Fraser River, yielding marine‐ and river‐collected groups, respectively ( N = 185). Fish were exposed to a mild (seine) or severe (gill net) fishery treatment at collection, and then held in flow‐through freshwater tanks for up to four weeks at historical (14°C) or projected migration temperatures (18°C). Using weekly nonlethal gill biopsies and high‐throughput qPCR, we quantified loads of up to 46 pathogens with host stress and immune gene expression. Marine‐collected fish had less severe infections than river‐collected fish, a short migration distance (100 km, 5–7 days) that produced profound infection differences. At 14°C, river‐collected fish survived 1–2 weeks less than marine‐collected fish. All fish held at 18°C died within 4 weeks unless they experienced minimal handling. Gene expression correlated with infections in river‐collected fish, while marine‐collected fish were more stressor‐responsive. Cumulative stressors were detrimental regardless of infections or collection location, probably due to extreme physiological disturbance. Because river‐derived infections correlated with single stressor responses, river entry probably decreases stressor resilience of adult salmon by altering both physiology and pathogen burdens, which redirect host responses toward disease resistance.

Practising everyday climate cultures: understanding the cultural politics of climate change - Michael K. Goodman; Julie Doyle; Nathan Farrell (Climatic Change, 2020)

The cultural politics of climate branding: Project Sunlight, the biopolitics of climate care and the socialisation of the everyday sustainable consumption practices of citizens-consumers - Julie Doyle; Nathan Farrell; Michael K. Goodman (Climatic Change, 2020)

COVID-19 and Pacific food system resilience: opportunities to build a robust response - Penny Farrell; Anne Marie Thow; Jillian Tutuo Wate; Nichol Nonga; Penina Vatucawaqa; Tom Brewer; Michael K. Sharp; Anna Farmery; Helen Trevena; Erica Reeve; Hampus Eriksson; Itziar Gonzalez; et al. (Food Security, 2020)

Production and characterisation of activated carbon and carbon nanotubes from potato peel waste and their application in heavy metal removal. - Ahmed I. Osman; Jacob Blewitt; Jehad K. Abu-Dahrieh; Charlie Farrell; Ala’a H. Al-Muhtaseb; John Harrison; David W. Rooney (Environmental Science and Pollution Research, 2019)
Herein, activated carbon (AC) and carbon nanotubes (CNTs) were synthesised from potato peel waste (PPW). Different ACs were synthesised via two activation steps: firstly, with phosphoric acid (designated PP) and then using potassium hydroxide (designated PK). The AC produced after the two activation steps showed a surface area as high as 833 m 2 g −1 with a pore volume of 0.44 cm 3 g −1 , where the raw material of PPW showed a surface area < 4 m 2 g −1 . This can help aid and facilitate the concept of the circular economy by effectively up-cycling and valorising waste lignocellulosic biomass such as potato peel waste to high surface area AC and subsequently, multi-walled carbon nanotubes (MWCNTs). Consequently, MWCNTs were prepared from the produced AC by mixing it with the nitrogen-based material melamine and iron precursor, iron (III) oxalate hexahydrate. This produced hydrophilic multi-wall carbon nanotubes (MWCNTs) with a water contact angle of θ = 14.97 °. Both AC and CNT materials were used in heavy metal removal (HMR) where the maximum lead absorption was observed for sample PK with a 84% removal capacity after the first hour of testing. This result signifies that the synthesis of these up-cycled materials can have applications in areas such as wastewater treatment or other conventional AC/CNT end uses with a rapid cycle time in a two-fold approach to improve the eco-friendly synthesis of such value-added products and the circular economy from a significant waste stream, i.e., PPW.

Can the turgor loss point be used to assess drought response to select plants for green roofs in hot and dry climates? - Pengzhen Du; Stefan K. Arndt; Claire Farrell (Plant and Soil, 2019)

Variation in Detrital Resource Stoichiometry Signals Differential Carbon to Nutrient Limitation for Stream Consumers Across Biomes - Kaitlin J. Farrell; Amy D. Rosemond; John S. Kominoski; Sophia M. Bonjour; Janine Rüegg; Lauren E. Koenig; Christina L. Baker; Matt T. Trentman; Tamara K. Harms; William H. McDowell (Ecosystems, 2018)

Reflex regulation of breathing by the paratrigeminal nucleus via multiple bulbar circuits - Alexandria K. Driessen; Michael J. Farrell; Mathias Dutschmann; Davor Stanic; Alice E. McGovern; Stuart B. Mazzone (Brain Structure and Function, 2018)

Ameliorating the adverse cardiorespiratory effects of chemical immobilization by inducing general anaesthesia in sheep and goats: implications for physiological studies of large wild mammals - Adian Izwan; Edward P. Snelling; Roger S. Seymour; Leith C. R. Meyer; Andrea Fuller; Anna Haw; Duncan Mitchell; Anthony P. Farrell; Mary-Ann Costello; Shane K. Maloney (Journal of Comparative Physiology B, 2018)

Adolescent cannabinoid exposure effects on natural reward seeking and learning in rats - H. Schoch; M. Y. Huerta; C. M. Ruiz; M. R. Farrell; K. M. Jung; J. J. Huang; R. R. Campbell; D. Piomelli; S. V. Mahler (Psychopharmacology, 2018)

Exploring tropical fisheries through fishers’ perceptions: Fishing down the food web in the Tonlé Sap, Cambodia - K. B. KC; N. Bond; E. D. G. Fraser; V. Elliott; T. Farrell; K. McCann; N. Rooney; C. Bieg (Fisheries Management and Ecology, 2017)
Tropical fisheries are among the most productive fisheries in the world, often providing the primary source of protein for the local population. Despite their importance, data on these systems are relatively limited, thus hampering management and policy development. Here, the implications of increasing fishing pressure are explored by critically evaluating the perceptions of the fishers who rely on these ecosystems to survive. A total of 169 fishers in 26 different fish‐dependent communities in the Tonlé Sap Lake, Cambodia, were surveyed to understand their perceptions of the impact that fishing has had on the ecosystem. The Tonlé Sap is one of the largest, yet poorest studied, freshwater fisheries in the world. Consistent with “fishing down the food web” theory of fisheries, survey data revealed that although fishers observed the total size of fish catch remaining consistent over recent years there has been a drastic decline in the size of individual fish, as well as a reduction in the diversity of species caught. These perceptions are examined with reference to food web theories that explore how fishing pressure leads to ecosystem change, including the more recent “indiscriminate fisheries” theory.

Aging, frailty and complex networks - A. B. Mitnitski; A. D. Rutenberg; S. Farrell; K. Rockwood (Biogerontology, 2017)

Responses of a Federally Endangered Songbird to Understory Thinning in Oak-Juniper Woodlands - Ashley M. Long; Mike E. Marshall; Michael L. Morrison; K. Brian Hays; Shannon L. Farrell (Environmental Management, 2017)

Determinants of coronary blood flow in sandbar sharks, Carcharhinus plumbeus - Georgina K. Cox; Richard W. Brill; Kaitlin A. Bonaro; Anthony P. Farrell (Journal of Comparative Physiology B, 2017)

Mouse genome annotation by the RefSeq project - Kelly M. McGarvey; Tamara Goldfarb; Eric Cox; Catherine M. Farrell; Tripti Gupta; Vinita S. Joardar; Vamsi K. Kodali; Michael R. Murphy; Nuala A. O’Leary; Shashikant Pujar; Bhanu Rajput; Sanjida H. Rangwala; et al. (Mammalian Genome, 2015)
Complete and accurate annotation of the mouse genome is critical to the advancement of research conducted on this important model organism. The National Center for Biotechnology Information (NCBI) develops and maintains many useful resources to assist the mouse research community. In particular, the reference sequence (RefSeq) database provides high-quality annotation of multiple mouse genome assemblies using a combinatorial approach that leverages computation, manual curation, and collaboration. Implementation of this conservative and rigorous approach, which focuses on representation of only full-length and non-redundant data, produces high-quality annotation products. RefSeq records explicitly link sequences to current knowledge in a timely manner, updating public records regularly and rapidly in response to nomenclature updates, addition of new relevant publications, collaborator discussion, and user feedback. Whole genome re-annotation is also conducted at least every 12–18 months, and often more frequently in response to assembly updates or availability of informative data. This article highlights key features and advantages of RefSeq genome annotation products and presents an overview of NCBI processes to generate these data. Further discussion of NCBI’s resources highlights useful features and the best methods for accessing our data.

Cardiorespiratory responses to haemolytic anaemia in rainbow trout Oncorhynchus mykiss - D. K. Gold; T. Loirat; A. P. Farrell (Journal of Fish Biology, 2015)
To quantify cardiorespiratory response to experimental anaemia in rainbow trout Oncorhynchus mykiss , a 24 h phenylhydrazine treatment was used to reduce haematocrit to almost one third of its initial value over 4–5 days. In response, relative blood velocity in the ventral aorta (an index of cardiac output) progressively increased to more than double to its normocythaemic value and there was no significant change in routine oxygen uptake. Thus, the primary compensatory response to anaemia was an increase in cardiac output.

Genetic Differentiation in Response to Selection for Water-Soluble Carbohydrate Content in Perennial Ryegrass (Lolium perenne L.) - J. A. Gallagher; L. B. Turner; A. J. Cairns; M. Farrell; J. A. Lovatt; K. Skøt; I. P. Armstead; M. O. Humphreys; I. Roldan-Ruiz (BioEnergy Research, 2015)

Facing warm temperatures during migration: cardiac mRNA responses of two adult Oncorhynchus nerka populations to warming and swimming challenges - K. Anttila; E. J. Eliason; K. H. Kaukinen; K. M. Miller; A. P. Farrell (Journal of Fish Biology, 2014)
The main findings of the current study were that exposing adult sockeye salmon Onchorhynchus nerka to a warm temperature that they regularly encounter during their river migration induced a heat shock response at an mRNA level, and this response was exacerbated with forced swimming. Similar to the heat shock response, increased immune defence‐related responses were also observed after warm temperature treatment and with a swimming challenge in two different populations (Chilko and Nechako), but with some important differences. Microarray analyses revealed that 347 genes were differentially expressed between the cold (12–13° C) and warm (18–19° C) treated fish, with stress response ( GO :0006950) and response to fungus ( GO :0009620) elevated with warm treatment, while expression for genes involved in oxidative phosphorylation ( GO :0006119) and electron transport chain ( GO :0022900) elevated for cold‐treated fish. Analysis of single genes with real‐time quantitative PCR revealed that temperature had the most significant effect on mRNA expression levels, with swimming and population having secondary influences. Warm temperature treatment for the Chilko population induced expression of heat shock protein ( hsp ) 90α , hsp90β and hsp30 as well as interferon‐inducible protein . The Nechako population, which is known to have a narrower thermal tolerance window than the Chilko population, showed even more pronounced stress responses to the warm treatment and there was significant interaction between population and temperature treatment for hsp90β expression. Moreover, significant interactions were noted between temperature treatment and swimming challenge for hsp90α and hsp30 , and while swimming challenge alone increased expression of these hsp s, the expression levels were significantly elevated in warm‐treated fish swum to exhaustion. In conclusion, it seems that adult O. nerka currently encounter conditions that induce several cellular defence mechanisms during their once‐in‐the‐lifetime migration. As river temperatures continue to increase, it remains to be seen whether or not these cellular defences provide sufficient protection for all O. nerka populations.

Upper thermal tolerance of closely related Danio species - R. Sidhu; K. Anttila; A. P. Farrell (Journal of Fish Biology, 2014)
The main finding of this study was that measuring maximum heart rate during incremental warming was an effective tool to estimate upper thermal limits in three small cyprinid Danio species, which differed significantly. Arrhenius breakpoint temperature for maximum heart rate, purportedly an index of optimum temperature, was 21·2 ± 0·4, 20·1 ± 0·4 and 18·9 ± 0·8° C (mean ± s.e .) for zebrafish Danio rerio , pearl danio Danio albolineatus and glowlight danio Danio choprae , respectively. The temperature where cardiac arrhythmias were first induced during warming ( T arr ) was 36·6 ± 0·7, 36·9 ± 0·8 and 33·2 ± 0·8° C (mean ± s.e .) and critical thermal maximum ( T Cm ) was 39·9 ± 0·1, 38·9 ± 0·1 and 37·2 ± 0·1° C (mean ± s.e .) for D. rerio , D. albolineatus and D. choprae , respectively. The finding that T arr was consistently 3–4° C lower than T Cm suggests that collapse of the cardiac life support system may be a critical trigger for upper temperature tolerance. The upper thermal limits established here, which correlate well with a broad natural environmental temperature range for D. rerio and a narrow one for D. choprae , suggest that upper thermal tolerance may be a genetic trait even among closely related species acclimated to common temperatures.

High water users can be drought tolerant: using physiological traits for green roof plant selection - Claire Farrell; Christopher Szota; Nicholas S. G. Williams; Stefan K. Arndt (Plant and Soil, 2013)

Commitment to the environment and student support for “green” campus initiatives - Anthony E. Coy; Allison K. Farrell; Katharine P. Gilson; Jody L. Davis; Benjamin Le (Journal of Environmental Studies and Sciences, 2013)

Effects of exogenous abscisic acid and gibberellic acid on pre-maturity α-amylase formation in wheat grains - K. R. Kondhare; P. S. Kettlewell; A. D. Farrell; P. Hedden; J. M. Monaghan (Euphytica, 2012)

Intercropping Caragana arborescens with Salix miyabeana to Satisfy Nitrogen Demand and Maximize Growth - Judicaël Moukoumi; Richard E. Farrell; Ken J. C. Van Rees; Russell K. Hynes; Nicolas Bélanger (BioEnergy Research, 2012)

Dead fish swimming: a review of research on the early migration and high premature mortality in adult Fraser River sockeye salmon Oncorhynchus nerka - S. G. Hinch; S. J. Cooke; A. P. Farrell; K. M. Miller; M. Lapointe; D. A. Patterson (Journal of Fish Biology, 2012)
Adult sockeye salmon Oncorhynchus nerka destined for the Fraser River, British Columbia are some of the most economically important populations but changes in the timing of their homeward migration have led to management challenges and conservation concerns. After a directed migration from the open ocean to the coast, this group historically would mill just off shore for 3–6 weeks prior to migrating up the Fraser River. This milling behaviour changed abruptly in 1995 and thereafter, decreasing to only a few days in some years (termed early migration), with dramatic consequences that have necessitated risk‐averse management strategies. Early migrating fish consistently suffer extremely high mortality (exceeding 90% in some years) during freshwater migration and on spawning grounds prior to spawning. This synthesis examines multidisciplinary, collaborative research aimed at understanding what triggers early migration, why it results in high mortality, and how fisheries managers can utilize these scientific results. Tissue analyses from thousands of O. nerka captured along their migration trajectory from ocean to spawning grounds, including hundreds that were tracked with biotelemetry, have revealed that early migrants are more reproductively advanced and ill‐prepared for osmoregulatory transition upon their entry into fresh water. Gene array profiles indicate that many early migrants are also immunocompromised and stressed, carrying a genomic profile consistent with a viral infection. The causes of these physiological changes are still under investigation. Early migration brings O. nerka into the river when it is 3–6° C warmer than historical norms, which for some late‐run populations approaches or exceeds their critical maxima leading to the collapse of metabolic and cardiac scope, and mortality. As peak spawning dates have not changed, the surviving early migrants tend to mill in warm lakes near to spawning areas. These results in the accumulation of many more thermal units and longer exposures to freshwater diseases and parasites compared to fish that delay freshwater entry by milling in the cool ocean environment. Experiments have confirmed that thermally driven processes are a primary cause of mortality for early‐entry migrants. The Fraser River late‐run O. nerka early migration phenomenon illustrates the complex links that exist between salmonid physiology, behaviour and environment and the pivotal role that water temperature can have on population‐specific migration survival.

Using maximum heart rate as a rapid screening tool to determine optimum temperature for aerobic scope in Pacific salmon Oncorhynchus spp. - M. T. Casselman; K. Anttila; A. P. Farrell (Journal of Fish Biology, 2012)
The mean ± s.e. optimum temperature ( T opt ) for aerobic scope in juvenile coho salmon Oncorhynchus kisutch was determined to be 17·0 ± 0·7° C. The repeated measures protocol took 3 weeks to complete the T opt determination using 12 fish tested at five temperatures separated by 2° C increments. This experiment also demonstrated that the T opt was associated with maximum heart rate ( f H ) failing to maintain a Q 10 ‐related increase with temperature. When maximum f H was produced in anaesthetized fish with pharmacological stimulation and f H measured from electrocardiogram recordings during acute warming, the Arrhenius break temperature (ABT) for Q 10 discontinuities in maximum f H (mean ± s.e . = 17·1 ± 0·5° C for 15 ppm clove oil and 16·5 ± 0·2° C for 50 ppm MS‐222) was statistically indistinguishable from the T opt measured using aerobic scope. Such a determination took only 3 days rather than 3 weeks. Therefore, it is proposed that determining ABT for discontinuities in maximum f H in anaesthetized fish presents itself as a valuable, high‐throughput screening tool to assess T opt in fishes, a metric that has become recognized as being extremely valuable in fish biology and fisheries management.

Platinum anticancer agents and antidepressants: desipramine enhances platinum-based cytotoxicity in human colon cancer cells - Peyman Kabolizadeh; Brigitte J. Engelmann; Nicholas Pullen; Jennifer K. Stewart; John J. Ryan; Nicholas P. Farrell (JBIC Journal of Biological Inorganic Chemistry, 2012)

Anoxic survival of the Pacific hagfish (Eptatretus stoutii) - Georgina K. Cox; Eric Sandblom; Jeffrey G. Richards; Anthony P. Farrell (Journal of Comparative Physiology B, 2011)

Challenges and Opportunities in Establishing Scientific and Regulatory Standards for Assuring Therapeutic Equivalence of Modified Release Products: Workshop Summary Report - Mei-Ling Chen; Vinod P. Shah; Derek Ganes; Kamal K. Midha; James Caro; Prabu Nambiar; Mario L. Rocci; Avinash G. Thombre; Bertil Abrahamsson; Dale Conner; Barbara Davit; Paul Fackler; et al. (The AAPS Journal, 2010)

Recent ecological trends in lower trophic levels of the international section of the St. Lawrence River: a comparison of the 1970s to the 2000s - J. M. Farrell; K. T. Holeck; E. L. Mills; C. E. Hoffman; V. J. Patil (Hydrobiologia, 2010)

Reproduction in an invasive exotic catfish Pterygoplichthys disjunctivus in Volusia Blue Spring, Florida, U.S.A. - M. A. Gibbs; J. H. Shields; D. W. Lock; K. M. Talmadge; T. M. Farrell (Journal of Fish Biology, 2008)
Morphology and reproductive strategies of a population of invasive loricariid catfish, Pterygoplichthys disjunctivus , in Volusia Blue Spring, Florida, were examined using morphological characters, gonado‐somatic indices and batch fecundity. This species has cystovarian ovaries, a left ovary that is significantly larger than the right ovary, and is highly fecund. Ovaries contained multiple oocyte size classes and completely spent females were not found, both of which indicate that this species is a multiple spawner. Reproductive patterns changed significantly between the first (2005) and the last (2007) years of this study; female fish became capable of spawning at a smaller size, a greater proportion of the captured population were capable of spawning each year and female batch fecundity increased, as did male and female gonado‐somatic indices. Plasticity of P. disjunctivus reproductive patterns is discussed in relation to resource availability and environmental stability.

Air breathing minimizes post‐exercise lactate load in the tropical Pacific tarpon, Megalops cyprinoides Broussonet 1782 but oxygen debt is repaid by aquatic breathing - R. M. G. Wells; J. Baldwin; R. S. Seymour; K. A. Christian; A. P. Farrell (Journal of Fish Biology, 2007)
Swimming in a flume at reduced water pO 2 resulted in muscle and blood lactate levels in Pacific tarpon Megalops cyprinoides that were significantly higher when fish did not have access to air. Blood glucose and haematological variables were unchanged throughout the regimes of exercise at two swimming speeds and hypoxia. Strenuous exercise with bouts of burst swimming, however, resulted in both high blood lactate and glucose, and perturbed haematological status with elevated haemoglobin and reduced mean cell‐haemoglobin concentration. Post‐exercise recovery was achieved through aquatic breathing rather than by air breathing. The air‐breathing organ in Pacific tarpon therefore prolonged aerobic activity, but gill breathing was used to repay oxygen debt.

Coupling non‐invasive physiological assessments with telemetry to understand inter‐individual variation in behaviour and survivorship of sockeye salmon: development and validation of a technique - S. J. Cooke; G. T. Crossin; D. A. Patterson; K. K. English; S. G. Hinch; J. L. Young; R. F. Alexander; M. C. Healey; G. Van Der Kraak; A. P. Farrell (Journal of Fish Biology, 2005)
Approximately 200 km from the mouth of the Fraser River, British Columbia, Canada, adult sockeye salmon Oncorhynchus nerka , were gastrically implanted with radio transmitters without anaesthetic. Subsets of the transmitter implanted fish were also biopsied which included drawing blood from the caudal peduncle (3 ml), removal of gill tissue (0·03 g) and quantification of energetic status using a microwave fat meter. Several experiments were used to test the hypothesis that the biopsy had a negligible effect on the subsequent survival and migratory behaviour of transmitter implanted fish. In the first experiment, no difference was found in the survival (both 100%) or tag retention (both 100%) between the two treatment groups (transmitter implanted with and without biopsy) when fish were held in pens for 24 h in the marine environment. Similarly, in other experiments where fish were released to the ocean to resume their migratory journey, no statistical differences were found in the travel times of fish in the two treatment groups, or in the proportion of fish that passed in‐river telemetry checkpoints. These results indicated that the handling and biopsy methods produced similar levels of mortality and tag retention as the telemetry treatment alone and that any changes in behaviour between the two treatment groups did not adversely affect migration time. Based upon the evidence provided from the biotelemetry of >300 adult sockeye salmon, it was felt that this general type of approach could be applicable to other fish species.

The pharmacokinetics of erythropoietin in the cerebrospinal fluid after intravenous administration of recombinant human erythropoietin - Anargyros Xenocostas; Wing K. Cheung; Francis Farrell; Cindy Zakszewski; Marian Kelley; Andrzej Lutynski; Michael Crump; Jeffrey H. Lipton; Thomas L. Kiss; Catherine Y. Lau; Hans A. Messner (European Journal of Clinical Pharmacology, 2005)

The relationships between fish health, metabolic rate, swimming performance and recovery in return‐run sockeye salmon, Oncorhynchus nerka (Walbaum) - K B Tierney; A P Farrell (Journal of Fish Diseases, 2004)
The repeat swimming ability and oxygen uptake ( M o 2 ) of adult sockeye salmon, Oncorhynchus nerka (Walbaum), were assessed at ambient water temperatures at three field locations along their migration route. Following these measurements, internal and external fish condition was evaluated according to United States Environmental Protection Agency guidelines. Here we report on the physiological characteristics of fish having either moderate or severe levels of disease and injury. Routine oxygen uptake ( M o 2 ) did not differ between healthy fish and those with indices of ill health. In contrast, fish classified as sick, which included conditions of damaged internal organs, an Ichthyophonus spp. heart infection, a Saprolegnia spp. gill infection, and skin wounds, had a lower post‐exercise M o 2 and were unable to repeat their critical swim speed ( U crit ) on the second swim test. Moderate levels of disease or injury did not significantly affect either U crit or post‐exercise M o 2 . We conclude that the ability of adult salmon to recover quickly from exercise may be a useful indicator of sublethal pathologies.

The differential leucocyte landscape of four teleosts: juvenile Oncorhynchus kisutch , Clupea pallasi , Culaea inconstans and Pimephales promelas - K. B. Tierney; A. P. Farrell; C. J. Kennedy (Journal of Fish Biology, 2004)
The appearance and proportions of morphologically distinct leucocytes (monocytes, thrombocytes, lymphocytes and diverse forms of granulocytes) encountered in the blood of four teleost species: coho salmon Oncorhynchus kisutch , Pacific herring Clupea pallasi , brook stickleback Culaea inconstans and fathead minnow Pimephales promelas , are presented, along with examples of how water quality influenced their relative proportions. The results clearly show that relative leucocyte number responds significantly and differently to changes in water quality. The value of using differential white cell counting as a quick and inexpensive component of assaying immune system alterations is discussed.

SU11248 inhibits tumor growth and CSF-1R-dependent osteolysis in an experimental breast cancer bone metastasis model - Lesley J. Murray; Tinya J. Abrams; Kelly R. Long; Theresa J. Ngai; Lisa M. Olson; Weiru Hong; Paul K. Keast; Jacqueline A. Brassard; Anne Marie O'Farrell; Julie M. Cherrington; Nancy K. Pryer (Clinical & Experimental Metastasis, 2003)

Field‐based measurements of oxygen uptake and swimming performance with adult Pacific salmon using a mobile respirometer swim tunnel - A. P. Farrell; C. G. Lee; K. Tierney; A. Hodaly; S. Clutterham; M. Healey; S. Hinch; A. Lotto (Journal of Fish Biology, 2003)
Novel field measurements of critical swimming speed ( U crit ) and oxygen uptake ( M o 2 ) in three species of adult Pacific salmon Oncorhynchus spp. up to 3·5 kg in body mass were made using two newly designed, mobile Brett‐type swim tunnel respirometers sited at a number of field locations in British Columbia, Canada. Measurements of U crit , which ranged from 1· 68 to 2·17 body lengths s −1 , and maximum M o 2 , which ranged from 8·74 to 12·63 mg O 2 kg −1 min −1 depending on the species and field location, were judged to be of similar quality when compared with available data for laboratory‐based studies. Therefore high quality respirometry studies were possible in the field using adult wild swimming salmonids. In addition, the recovery of wild adult Pacific salmon from the exhaustive U crit swim test was sufficiently rapid that swimming performance could be repeated with M o 2 being reestablished. This result suggests that wild adult salmon are capable of carrying a moderate excess post‐exercise oxygen consumption without adversely affecting U crit , maximum M o 2 or swimming economy. Such capabilities may be extremely important for timely migratory passages when salmonids face repetitive hydraulic challenges on their upstream migration.

Comparison of results from several AOGCMs for global and regional sea-level change 1900-2100 - J. M. Gregory; J. A. Church; G. J. Boer; K. W. Dixon; G. M. Flato; D. R. Jackett; J. A. Lowe; S. P. O'Farrell; E. Roeckner; G. L. Russell; R. J. Stouffer; M. Winton (Climate Dynamics, 2001)

Influence of earthworms on soil properties and grass production in reclaimed cutover peat - K. E. Boyle; J. P. Curry; E. P. Farrell (Biology and Fertility of Soils, 1997)